Rancang Bangun Aplikasi Katalog Augmented Reality Design Setup Ruang Kerja Minimalis berbasis Android - ST. Aminah Dinayati Ghani; Andi Alfian (AGENTS: Journal of Artificial Intelligence and Data Science, 2023)
This research is motivated by the use of Augmented Reality on the catalog page which can help clients see visualizations of the Interior design of a minimalist workspace based on the desired Interior theme in 3-dimensional form. The problem that arises is how to build an application that can scan 3D objects on catalog pages along with interesting workspace concept information by utilizing Android-based devices. The purpose of this study is to design a catalog information media that can display the Interior design of a minimalist workspace by utilizing Augmented Reality features into Android-based devices. This application was created using the C# programming language and uses Unity 3D Engine, SketchUp, and Photoshop software. Functionally testing the software on catalog applications using the blackbox method. The applications resulting from this research can help clients see the theme of minimalist workspace design designed to attract clients' attention in visualizing into the form of 3D objects